Multi-directional matrix converter for low power application using field-programmable gate array - Toosi, Saman (2015)
With high robustness nature and simplicity design, the stand alone battery based systems found their way to supplies a remote local village or individual users. In modern stand-alone power system, power electronic converters have significant effect on system performance. Due to the rapid progress in power electronic component and integrated power modules, the power converters become a commercial alternative for modern low power applications. This evolution encourages a progressive development of Stand-Alone Battery Based System (SABBS) by reducing the number of converters and using the power of input sources in different operation modes. In this study, the Multi-Directional Matrix Converter (MDMC) was developed using the five expected operation mode of stand-alone battery based system. Based on the conventional matrix converter structure, five configurations were proposed to control the power direction from power sources to loads. The indirect method with Space Vector Pulse Width Modulation (SVPWM) technique applied to the proposed MDMC configurations. However, the SVPWM could not inject power from generator and battery at the same time, since several vectors were utilized in one switching period. Therefore, a novel modulation method introduced to change the function of MDMC from inverter to PWM rectifier, PWM rectifier to inverter, or inverter and PWM rectifier to inverter or PWM rectifier. The proposed modulation method acts based on average voltage over one switching period concept. Hence, in order to determine the duty ratio for each switch, the instantaneous input voltages are captured and compared with triangular waveform continuously. By selecting the proper switching pattern and changing the slope of the carriers, the sinusoidal input current can be synthesized with high power factor and desired output voltage. In the proposed model named Extended Direct Duty Pulse Width Modulation (EDDPWM) method, the number of time subinterval was increased to inject the power from the AC and DC sources to the load simultaneously. Thus, it increased the performance of the system and save more energy. These five configurations and two modulation methods were simulated using MATLAB software and the results compared in term of THD, DC current ripple and ability to work in different operation modes. Based on the simulation results, the neutral connection MDMC with EDDPWM technique generated a set of digital commutation signals which are applicable for all operation modes. While, the switching signal set of SVPWM run the MDMC in one Mode at a time. The main emphasis in proposed full-silicon MDMC structure was minimizing the total number of bidirectional switches and subsystems to achieve higher operating efficiency and more compact designs, and to reduce weight and volume of the resultant systems. On the other hand, in this study the Xilinx’s System Generator development tool was used to implement the EDDPWM method in FPGA. Moreover, high level design tools were employed to decrease the development time required for implementing the modulation methods in FPGA. This study also derived necessary equation for proposed modulation method as well as detail of analysis and modulation algorithm. The theoretical and modulation concepts have been verified in MATLAB simulation and experimental test.